(untitled) (Canadian Perspectives on Academic Integrity, 2020)
In this article, we, as representatives from several post-secondary institutions across Manitoba and British Columbia, describe how sharing knowledge and experiences across institutions has informed and enhanced academic integrity initiatives at our respective institutions. We outline how participation in provincial, national, and international teaching and learning events as a collective has informed our work in academic integrity and led to the emergence of the Manitoba Academic Integrity Network (MAIN) in May 2019. We discuss the benefits of collaborating within a provincial network and next steps for expanding the reach of the network across institutions by engaging faculty, staff, and students.